Bay ‘Al-Tawarruq dan Aplikasinya di Bank Muamalat Malaysia Berhad - Mahyudin, M. I.; Che Seman, A. (Universiti Sains Islam Malaysia, 2024)
A study of the Islamic banking products especially in the implementation of bay‘ al- tawarruq transaction shows that the purpose of that transaction is to provide liquidity to the customer such as personal financing, working capital expenditure, cash lines and credit card. However as the industry expanded widely, there is innovative effort taken by industry player by extending the products to involve investment and deposit instrument that provide fixed return to the customer. As a second full fledged Islamic bank in Malaysia, Bank Muamalat Malaysia Berhad (BMMB) is also involved in offering products based on bay‘ al- tawarruq concept. Hence, this study intends to study the original principles of bay‘ al- tawarruq contract and its current applications in BMMB. The data is obtained from two sources, secondary sources and primary sources. Among the secondary sources used are data from libraries, reference materials such as books, papers, journals and newspaper. For primary sources, researcher used interviews with respective staff in BMMB. The study found that the bay‘ al-tawarruq contract has been adopted as an alternative to replace bay‘ al-‘īnah contract especially for financing based products offered in BMMB.